Symmetry breaking in the body-fixed electron emission pattern due to electron-retroaction in the photodissociation of H+2 and D+2 close to threshold - Heck, S.; Gatton, A.; Larsen, K. A.; Iskandar, W.; Champenois, E. G.; Strom, R.; Landers, A.; Reedy, D.; Dailey, C.; Williams, J. B.; Severt, T.; Jochim, B.; et al. (My University, 2019)
We present an experimental investigation of symmetry breaking of H2 and D2 molecules after single photoionization due to the Coulomb field of the emitted slow electron interacting with the parent cation during dissociation. The experiments were carried out by measuring the three-dimensional momentum vectors of the photoelectron and recoiling ion in coincidence using a reaction microscope. For photon energies close to threshold, the low-energy photoelectron influences the dissociation process, which results in an asymmetric molecular frame photoelectron angular distribution. This can be explained by the retroaction of the Coulomb field of the photoelectron on its parent ion and has been recently experimentally demonstrated by M. Waitz et al. [Phys. Rev. Lett. 116, 043001 (2016)], confirming theoretical predictions by V. V. Serov and A. S. Kheifets [Phys. Rev. A 89, 031402(R) (2014)]. High-momentum resolution and a new series of photon energies just above the dissociation threshold enable the observation of a strong influence of the electron energy and nuclear kinetic energy on the electron localization process for energies below ∼100 meV, which so far has neither been observed nor discussed by theory. Exploring the limitations of the retroaction mechanism at our lowest photon energy, we are able to single out a sensitive testbed and present data of non-Born-Oppenheimer dynamics of the simplest molecular system for future benchmark computational treatments.